Establishing a field epidemiology elective for medical students in Kenya: A strategy for increasing public health awareness and workforce capacity. Issue 1 (March 2015) - Arvelo, Wences; Gura, Zeinab; Amwayi, Samuel; Wiersma, Petra; Omolo, Jared; Becknell, Steven; Jones, Donna; Ongore, Dismas; Dicker, Richard
Abstract: Medical students have limited exposure to field epidemiology, even though will assume public health roles after graduation. We established a 10-week elective in field epidemiology during medical school. Students attended one-week didactic sessions on epidemiology, and nine weeks in field placement sites. We administered pre- and post-tests to evaluate the training. We enrolled 34 students in 2011 and 2012. In 2011, we enrolled five of 24 applicants from a class of 280 medical students. In 2012, we enrolled 18 of 81 applicants from a class of 360 students; plus 11 who participated in the didactic sessions only. Among the 34 students who completed the didactic sessions, 74% were male, and their median age was 24 years (range: 22–26). The median pre-test score was 64% (range: 47–88%) and the median post-test score was 82% (range: 72–100%). Successful completion of the field projects was 100%. Six (30%) students were not aware of public health as a career option before this elective, 56% rated the field experience as outstanding, and 100% reported it increased their understanding of epidemiology. Implementing an elective in field epidemiology within the medical training is a highly acceptable strategy to increase awareness for public health among medical students.